Higher Serum Bilirubin Levels in Response to Higher Carbohydrate Intake During Early Pregnancy and Lower Gestational Diabetes Mellitus Occurrence in Overweight and Obese Gravidae - He, Wennan; Wang, Liping; Zhang, Yi; Jiang, Yuan; Chen, Xiaotian; Wang, Yin; Dou, Yalan; Chen, Hongyan; Yan, Weili (Frontiers in Nutrition, 2021)
Background and aim: Serum bilirubin levels are recently shown to be a novel protector of gestational diabetes mellitus (GDM), yet whether they could be affected by dietary carbohydrate is unclear. We aimed to examine the associations between dietary carbohydrate parameters with serum bilirubin levels during early pregnancy and later GDM onset in gravidae, with further exploration on a potential mediating role of serum bilirubin levels on carbohydrate parameters-GDM pathways. Methods: 260 healthy gravidae (BMI≥24kg/m2) derived from a historical cohort in two hospitals in China were included. The associations between carbohydrate parameters (total carbohydrate intake, GI, fibre intake, GL) with serum bilirubin levels (total bilirubin, TB and direct bilirubin, DB) and GDM were evaluated by multivariable regression analysis after adjusting for pre-defined confounders in directed acyclic graph (DAG). Generalized structural equation modelling (GSEM) was applied to perform adjusted mediation analysis. Results: After adjusting for confounders, increased serum bilirubin levels and decreased GDM occurrence were observed following dietary carbohydrate intake(%E) and GL(g/1000kcal) in highest tertile compared to the lowest tertile (carbohydrate: TB: β=1.129(95%CI: 0.260,1.997), DB: β=0.630(95%CI:0.265,0.996);GL:TB: β=1.388(95%CI: 0.549,2.228); DB: β=0.476(95%CI: 0.240,0.828; carbohydrate: adjusted OR=0.41(95%CI:0.18-0.93); GL: adjusted OR=0.38 (95%CI:0.17,0.86)). The mediating effect of carbohydrate intake and GL on GDM through bilirubin levels was evaluated as modest (carbohydrate: 8.4% for TB, 1.8% for DB; GL: 12.3% for TB, 3.4% for DB). No association was observed regarding GI and fibre with bilirubin or GDM. Conclusions: Our results suggested that the gravidae consuming higher total carbohydrate intake and GL in early pregnancy appeared to have higher serum bilirubin levels and lower GDM onset, with a potentially modest mediating effect of bilirubin levels on carbohydrate/GL-GDM pathways. Larger investigation is further needed for solid evidence.